2015
DOI: 10.1021/acsami.5b04421
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cu2ZnSnS4 Films with Modified Surface for Thin-Film Lithium-Ion Batteries

Abstract: Cu2ZnSnS4 (CZTS) is an important material in low-cost thin film solar cells and is also a promising candidate for lithium storage. In this work, a novel three-dimensional CZTS film coated with a lithium phosphorus oxynitride (LiPON) film is fabricated for the first time and is applied to thin-film lithium-ion batteries. The modified film exhibits an excellent performance of ∼900 mAh g(-1) (450 μAh cm(-2) μm(-1)), even after 75 cycles. Morphology integrity is still maintained after repeated lithiation/delithiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“… 4 Cu 2 MSnX 4 -based materials are also interesting candidates for a wide variety of other applications, including photodetectors, 5 photocatalysis, 6 hydrogen production, 7 photoelectrochemical cell, 8 and batteries. 9 …”
Section: Introductionmentioning
confidence: 99%
“… 4 Cu 2 MSnX 4 -based materials are also interesting candidates for a wide variety of other applications, including photodetectors, 5 photocatalysis, 6 hydrogen production, 7 photoelectrochemical cell, 8 and batteries. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence of multiple plateaus in the first delithiation, and a large change in electrochemical characteristics between the 1 st and 2 nd cycles,,, it was concluded that the individual metal sulfides (Cu 2 S, ZnS and SnS 2 ) rather than CZTS, were formed at this stage. In subsequent lithiations, the conversion process in Equation (3) therefore separates into Equations (6), (7) and : trueCu2S+2Li2Cu+Li2S trueSnS2+4Li4ptSn+2Li2S4pt trueZnS+2LiZn+Li2S4pt …”
Section: Resultsmentioning
confidence: 99%
“…As an illustration, we perform a thorough analysis of a CAM, dicopper zinc tin sulfide (Cu 2 ZnSnS 4 ) or CZTS. This material has achieved among the highest reported gravimetric capacities among CAMs,, and, notably, wide stoichiometric variations are possible, enabling modulation of the lithiation characteristics through facile synthetic techniques ,. Furthermore, the multi‐step nature of the lithiation/delithiation processes that occur over a wide voltage range during cycling of CZTS render it an ideal material with which to examine and compare these processes, and to illustrate the inadequate nature of CTPs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when HERs are conducted under extreme conditions, the NWD electrode remains intact, whereas the NOD electrode is completely peeled off after 10 min of reaction. [36] The degradation is mainly induced by the destruction or detachment of nanowalls from conducting substrates because of poor mechanical adhesion, [37] the occurrence of high volume stress at nanowall and substrate interfaces during reactions, [38] and the occurrence of corrosive chemical reactions when in contact with electrolytes. wileyonlinelibrary.com quaternary chalcogenides offer better options as they possess higher flexibility for tuning the material properties and the fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stability of nanowall structures serving as electrodes for EEC devices is questionable because such structures are easily degradable upon engaging in electrochemical reactions . The degradation is mainly induced by the destruction or detachment of nanowalls from conducting substrates because of poor mechanical adhesion, the occurrence of high volume stress at nanowall and substrate interfaces during reactions, and the occurrence of corrosive chemical reactions when in contact with electrolytes . Therefore, designing and engineering nanowall‐structured electrodes with outstanding stability for EEC devices remains a challenge.…”
Section: Introductionmentioning
confidence: 99%